Erosion rate model comparison of electrical discharge machining process - Yahya, Azli (IEEE, 2012)
This paper reports a comparison studies between two erosion rate model and experimental results of an Electrical Discharge Machining (EDM) process for high gap current. Two erosion rate models are Dimensional Analysis (DA) model and Artificial Neural Network (ANN) model that have been summarized from the previous author's publication. The data analysis is based on a copper electrode and steel workpiece materials. The result indicated that the ANN model provides better accuracy than the DA model when compared to the experimental results.